"What Happened to Our Face?” Reflection on the Subjectivity of Euro-American Ethnicity.: A Review of Ethnic Subjectivity in Intergenerational Memory Narratives: Politics of the Untold - Szélpál, Lívia (AMERICANA E-journal of American Studies in Hungary, 2019)
Ethnic Subjectivity in Intergenerational Memory Narratives: Politics of the Untold Mónika Fodor New York: Routledge; 1st Edition, 2019. 298 pages ISBN-13: 978-1138489837 ISBN-10: 1138489832